SELOKO AS A WEDDING ADVICE OF SAROLANGUN MALAY: THE DIRECTIVE FUNCTION AND VALUE OF CHARACTER - bambang prastio; Istiqomah Nurzafira; Ahmad Afriza Citrawida; Hanifah Hanifah (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2021)
Globalization era causes local wisdom such as seloko oral literature begins difficult to be found in certain events. Seloko is one of the oral traditions owned by Jambi Province. Seloko can be found in the event of marriage reception, custom event, officer inauguration, etc. This research aims to describe seloko utterance uttered in the Malay community's marriage event living in Sarolangun Regency. Particularly, this research aims to describe the function of seloko and educational values obtained in seloko. The research results show that there are three functions of seloko in marriage advice such as ordering, suggesting, and forbidding. Meanwhile, there are four values of character education in seloko. First, the religious value that relates to obeying the religion and custom. Second, the character value relates to oneself that covers social care, respecting other people, and loyal. Third, the self character value, which relates to society's environment that covers cooperation and democracy. Besides that, seloko can be used as a reference in running life because it contains the teaching and advice.